Cixin Liu’s ‘The Remembrance of Earth’s Past’ Trilogy: The End of All Things - Grzegorz Trębicki (Literatura i Kultura Popularna)
The present paper is the third in the series of articles devoted to the selected aspects of a modern science fiction genre variant that has previously been approximated as ‘the space opera of a great crisis,’ the remaining two publications being: ‘Trylogia Wspomnienie o przeszłości Ziemi Cixina Liu: w poszukiwaniu kontekstów interpretacyjnych’ [Cixin Liu’s The Remembrance of Earth’s Past Trilogy: In Search of Interpretative Grounds] and ‘Mariaż dwóch światów: quasi-chrześcijańska wizja ewolucji człowieka i kosmosu w Pieśniach Hyperiona Dana Simmonsa’ [The Marriage of Two Worlds: A Quasi-Christian Vision of the Evolution of the Universe and Humanity in Dan Simmons’ Hyperion Cantos]. The paper first provides a summary of the previous discussion, especially the modified description of the key generic traits of ‘the space opera of a great crisis,’ and then conducts a more detailed, comparative analysis of the two representative and essential, yet contrasting achievements of the genre in question: Liu’s trilogy The Remembrance of Earth’s Past and Simmon’s tetralogy Hyperion Cantos, in respect to the worldviews that inform them, respectively, as well as their narrative structures. It is suggested that the narrative structures of both works are considerably influenced by their respective worldviews and that, paradoxically, the apparently crude and simple narration of The Remembrance of Earth’s Past may be viewed as a conscious literary operation aimed at enhancing the trilogy’s message. Thus, (contrary to many previous critical opinions) Liu’s work proves to be not only a major extrapolative achievement but also an interesting artistic one.